DETERMINAN PARTISIPASI PENGGUNAAN KB MOP DI DKI JAKARTA PADA TAHUN 2021 - Diego Sergio Giasia Lumbantobing (2022)
Vasectomy is one type of long-term contraceptive method. In Indonesia, the level of participation of men in using contraceptives, especially vasectomy contraceptives is still very low. This study aimed at seeking the determinants of vasectomy participation among men. This is a quantitative study with a cross-sectional design conducted in the DKI Jakarta province, capital city of Indonesia in December 2021. The population in this study were men aged 25-59 years. The sample of this study was 140 men consisting of 40 vasectomy users in 2021 and 100 men who did not use vasectomy, using stratified random sampling technique. Data collected by using a questionnaire. There was a association between participation in the use of vasectomy with the number of children, income, knowledge, education level, and wife's support. The multivariate results show that the most influential determinant with participation in the use of vasectomy in DKI Jakarta is the number of children with a prevalence odd ratio (POR) value = 40.72. The conclusion of this study states that men with more than 2 children were more likely to participates in using vasectomy. It is highly recommended to provide education for men to attract them to use vasectomy.